Education, Freedom, and Emancipation from the Standpoint of the Recognition Theory - Krassimir Stojanov (Sisyphus, 2020)
In this interview, Axel Honneth discusses his views on education that leads to social freedom as the opposite of the currrently predominatly understanding of education as training for employability. He explains, in which sence social freedom as goal of education differs from autonomy and emancipation. Honneth also emphasises the significance of childrens’ imaginative powers for a democratic society.